STUDYING FACTORS INFLUENCING THE SERVICES MARKET IN LVIV REGION IN THE PANDEMIC PERIOD - Vasyltsiv N.М. (The actual problems of regional economy development, 2022)
The article presents findings of the research on the factors influencing the services market in Lviv region in the pandemic period. Relevance of the study on the services market is determined by its function of support for the balance of reproduction process that corresponds to the living standards by satisfying different demands of population, namely insurance, banking, and touristic services, etc. The goal of the article is to study and analyze the impact made by the factors on development of the services market in the current conditions and to substantiate the prospects of its development for the next two years. While making the research, the author used general scientific and special methods. Inductive and deductive methods were used to study the volume of provided services. The method of economic analysis and comparison was applied to analyze the services market in Ukraine and in Lviv region. Graphical method was used for visual demonstration of the expected indices of changes of the volume of services provided in Lviv region. To make theoretical generalization and conclusions, the author used the abstract and logical method. The article substantiates dynamics of total volumes of services production in Ukraine in 2017-2020 and points that the highest level of them was marked in 2019. The research also shows dynamics of the volume of services provided in Lviv region. It is determined that the total volume of services provided in 2021 increased by 41% as compared to 2020, whereas the volume of services provided for population – by 55%. The work names and analyzes external and internal factors influencing development/stagnation of the services market in Ukraine and in Lviv region. The author makes forecast on development of the services market in Lviv region. Basing on statistical data on the volume of services provided in Lviv region, the author has made a linear model of the forecast for 2022-2023. The article also supplies a calculated linear model of the forecast on volume of services provided for population in Lviv region in 2022-2023. The adequacy of both models is confirmed. It is proved that development of the services market will depend on the time of overcoming the general economic crises, caused by the pandemic, the martial law in Ukraine, as well as on the time of war finish. It is substantiated that the services market needs attraction of extra investments, including foreign ones.